BOOK REVIEW “IL FINANZIAMENTO DELLE START-UP INNOVATIVE (THE FINANCING OF INNOVATIVE START-UPS)”, BY LORIS L.M. NADOTTI, MANUELA GALLO, DUCCIO MARTELLI, VALERIA VANNONI, ISEDI, MILANO, 2023 - Pencarelli, Tonino (Piccola Impresa / Small Business, 2025)
The book addresses a crucial issue for the survival and development of innovative start-ups, especially in Italy, where the financial system can still be defined as bank-centric and where therefore the financing of new entrepreneurial initiatives is not simple. This is both due to the necessary attention to risk that traditional intermediaries adopt when granting loans, and due to the incomplete success of new entities and tools to meet the needs of new businesses. The book offers a complete overview of the offer of financing tools for innovative start-ups, also suggesting possible approaches for new businesses aimed at effectively requesting funds.